The Agrarian Law Policy in the Control of Residence by Expatriates in Indonesia - Corina Ealen Meilan Danu; Ketut Ketut Briliawati Permanasari; Wilujeng Wilujeng Jauharnani; Ria Ria Yunita Sari (Fakultas Hukum Universitas Airlangga, 2020)
The state has the right to control the land, waters and natural resources contained therein to achieve the greatest benefit of the people. According to the provisions of Article 9 paragraph (1) and Article 26 paragraph (2) of the Law of the Republic of Indonesia Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, property rights may only be owned by Indonesian citizens. Based on these conditions, expatriates cannot have a residence in Indonesia. On the other hand, Indonesia as a subject of international law has the responsibility in protecting the right of expatriates to dominate residence in Indonesia. In this study, the state responsibility for the provision of residence for foreigners and the regulations that provide space for expatriates in the mastery of residence in Indonesia will be discussed. In international law, there are principles of state responsibility. This principle mandates that the state guarantees protection of foreigners, including the place of residence for foreigners. The development of regulations in Indonesia provides a solution to the control of residence by expatriates. The legal solution offered is the control of residence with a tenancy agreement between expatriates and homeowners who are Indonesian citizens or by using the right of use. The right of use a residence given to the expatriates is in the form of a single house and apartment units that are limited by the price and area of land in accordance with the applicable regulations.